(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the current status of compliance with hand hygiene practices of medical staff at the Neonatal Intensive Care Unit at Hung Vuong Hospital in 2024. Subjects and methods: A cross-sectional study design was conducted among 32 medical staff, including doctors, nurses and midwives. The study conducted direct and indirect (camera-based) hand hygiene monitoring from September to December 2024. Results: The compliance rate of the “5 moments of hand hygiene” reached 95.6%. The rate of medical staff correctly performing all 6 hand hygiene steps reached 92%. The rate of staff washing their hands after contact with the patient’s environment was only 87.5%. Conclusion: The hospital has implemented effective interventions to improve the hand hygiene compliance rate of healthcare workers, contributing to infection prevention efforts in the Neonatal Intensive Care Unit setting.